DESAIN REAKTOR LIQUID-PHASE UNTUK PRODUKSI SINTESIS NANOPARTIKEL FE3O4 MENGGUNAKAN EKSTRAK DAUN SIRIH MERAH (piper crocatum) SEBAGAI CAPPING AGENT - Nyoman Ayu Kristinawati; Asep Bayu Dani Nandiyanto; Risti Ragadhita (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
The aim of this study was to design a liquid-phase reactor for the production of synthesized Fe3O4 nanoparticles using red betel leaf extract (Piper Crocatum) as a capping agent. The reactor model is assumed to have a production capacity of 60,000 tonnes per year, 220 tonnes per day at 2.680 kg/hour. The ratio of the amount of red betel leaf extract, FeCl3.6H2O, FeCl3.6H2O, and NaOH catalyst respectively is 20:8:4:1. Data analysis was obtained through manual calculations using the basic Microsoft Excel application. The selected reactor is a Continuous Stirred Tank Reactor (CSTR). Reactor volume (80%) is 325 ft3 with a height of 38.6 in. The dimensions of the stirrer (stirrer) are also calculated, the results of several parameters are the impeller diameter (Da) of 19.76 in, impeller height from tank bottom (c) of 13.5 in, impeller length (l) of 4.45 in and stirring power (p) of 4.33 hp. These results have not been analyzed in terms of thermodynamics such as ∆Hf and ∆Gf calculations to see whether the reaction is exothermic or endothermic, so it needs further study. However, the results of this analysis can be used as learning media in the process of designing, operating mechanisms and analyzing the performance of CSTR reactors.